Optimization of shrimp waste fermentation by Kocuria rosea to obtain a protein hydrolysate - Bertsch, Annalisse; Díaz, Isabel; Coello, Nereida (Rev. Téc. Fac. Ing. Univ. Zulia)
This assay was carried out to obtain a protein hydrolysate by optimization of culture conditions (pH, substrate concentration and temperature) for degrading the shrimp waste by Kocuria rosea using response surface methodology (MSR). The results of regression analysis showed that optimal culture conditions were substrate 138g/L; pH 7.57 and 38°C in 24 hours. The comparison between the optimized and non optimized fermentation process evidenced an increasing in 71%, 64%, 43% and 60% the concentration of soluble protein (mg/100mL), proteolytic activity (U/mL), N-acetyl-glucosamine (g/L) and chitinolytic activity (U/mL), respectively. The optimized culture broth was dehydrated and grounded to obtain protein hydrolysate (HP). This was composed by true protein (62.5%) with 94% in vitro digestibility, fat, ash and reducing sugars from chitin degradation. True protein content was improved in 36% respect to shrimp waste unfermented (HDC). This biotechnological process is a harmonious way with the ambient to revalorization of shrimp waste like feedstock.